Self-Reported Physical Activity, Injury, and Illness in Canadian Adolescent Ski Racers - Doyle-Baker, Patricia K.; Emery, Carolyn A. (Frontiers in Sports and Active Living, 2020)
Alpine ski racers spend a considerable amount of time on snow during the ski season and this may detract from other activities known to influence fundamental movement skills and overall health related outcomes. Parents of racers (n=52 F; n=44 M; age range 9.3-13.7 years) registered in an Alberta ski club in Canada were recruited to complete a baseline medical questionnaire at the start of preseason training in 2017. We describe the physical activity volume and sport participation level outside of physical education classes over the previous 12 months and report on the different injuries (fractures and concussion), medications (supplement use) and health care utilization. The mean number of activities participated over the previous 12 months was five (range of 1-14) and the top activities were cycling, hiking, and swimming. A cumulative mean of just under 400 hours of activity was reported, with different ranges between males (62-868.5) and females (27-1015). More males reported concussions over a lifetime, with alpine skiing accounting for 46% and mountain biking 15%. Over the past 12 months 18.4% of the athletes reported being injured and injury severity impacted return to sport with range of reported days missed from 1-60 days. Thirteen injuries were from alpine skiing and females (11.5%, 6/52) reporting more lower limb injuries than males (6.8% 3/44). Most athletes (85%) did not take medication on a regular basis and those that did had a medical diagnosis. The frequency of diagnosed respiratory conditions were 12.6% (12/95) with males reporting slightly more cases than females. No difference in the number of emergency visits (25%) between male and females occurred over the past 12 months however females reported more (n=102) allied health care, sport medicine visits and x-rays appointments when compared to males (n=65). In summary, the volume of activity reported was very high over the previous 12 months, therefore calculating total load should be considered since 10-14-year-old athletes are entering a growth period and may be at risk for overuse injuries. Employing wearable technology to quantify intensity and participation hours in combination with the self-report questionnaire would improve the accuracy of the data collected.